Environment, Market Share, and Market Power - Boulding, William; Staelin, Richard (Management Science, 1990)
In this paper we develop a process model relating market share to firm profits. In particular, we specify average price and average cost equations as a function of previous year market share position, changes in market share, environmental conditions, and interactions of environmental conditions with the lagged market position and market share change variables. We estimate these equations using PIMS data after controlling for unobservable factors. Our results suggest that firms with high market shares derive no extra market power benefits except if they operate in environments with little buyer power. Instead, environmental factors and changes in market share most strongly influence price and cost. An analysis of the market share associated with maximal firm profits indicates that for the majority of firms in our sample steadily increasing market share does not always associate with increasing profits, giving credence to the proposition that “more market share is not always better.”